The motivation of temporary sales people in selected IT / telecom companies in Hong Kong - Chan, Vincent Tuen-cheung (Curtin University, 2011)
This thesis narrates a story in the study of a phenomenon in the search of an explanation of the motivation of temporary sales people [promoter] in information technology and telecommunication companies in Hong Kong. The use of these non-permanent sales force in Hong Kong is becoming popular but there is a lack of guidelines for motivating them. Given the exploratory nature of the study and limited prior empirical research on the topic and organizational settings, a qualitative approach was adopted. Grounded research and modified grounded theory were used as a discovery tools to guide the overall study. Triangulation of data collection methods was used; and data were collected from both employers and employees from focus group and in-depth interviews. Constant comparative method was adopted in data analysis. Data were first compared to data and the resulting categories were compared to each other and to the extant motivational theories, rendering into a tentative conceptual framework. It was found that the promoters’ resources comprised internal resourcefulness and connectedness, along with the preemptive situational factors of organization, were fueling the promoters’ meaning-ascription and job-crafting motivation-process.